Veins that bulge: understanding rare venous aneurysm of the upper extremity: a case report - Bora, Rajib; Jain, Nitin; Ankur; Prabakaran, Rajeshwari (International Surgery Journal, 2025)
Venous aneurysm (VA) of upper extremity is an extremely rare condition in children. The reported incidence of upper limb VA is around 10% which mostly presents as an asymptomatic mass. Due to subtle clinical presentation and resemblance to common soft tissue lesions, evaluation of VA requires careful clinical examination with radiological imaging. We present a rare case of VA in a 16-year male in forearm involving the cephalic vein that was managed successfully with surgical excision.